Statins and cancers - Stryjkowska-Góra, Aleksandra; Karczmarek-Borowska, Bożenna; Góra, Tomasz; Krawczak, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2015)
Statins (inhibitors of 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase) are a group of drugs used to treat lipid disorders. They inhibit cholesterol synthesis at an early stage of the biosynthesis pathway, thus eliminating numerous metabolites involved in the cycle. Numerous studies point to different possible effects of statins on cancer cells. Statins inhibit growth of a tumor, invasion and metastasis formation. They block the production of isoprenoids, which are necessary for post-translational modifications of many proteins, including those involved in normal cell signaling. They also contribute to the reduction in the expression of vascular endothelial growth factor, sensitize tumor cells to NK cell activity, and modify the body inflammatory response. Due to different pharmacokinetic properties of individual statins, they may have opposite effects on the risk of cancer. Currently, most information on the effects of statins on the risk of developing cancer is obtained from observational studies. The studies have different results depending on the location of cancer. The protective effect of statins was observed in the meta-analysis of numerous studies including prostate cancer, stomach cancer, esophagus cancer, and hepatocellular carcinoma; however, it has not yet been confirmed that statins influence the risk of developing colorectal cancer, breast cancer, or lung cancer. The protective effect of statins on the development of many kinds of cancer can be a valuable and easy way to reduce morbidity. However, further research is necessary to thoroughly determine the value of this group of drugs.